The Essential guide to contemporary dance techniques - Clarke, Melanie (Marlborough, Wiltshire : The Crowood Press, 2020)
This book explores the multifaceted learning processes and underlying principles behind the technical skills and abilities of a contemporary dancer. The depth and complexity of this challenging sensorial, intellectual, reflective and creative process is presented with clarity, to support every training dancer in achieving the most from their learning experiences. Insights into three major technical forms: Graham technique, Cunningham technique and Release-based technique, reveal the distinct approaches, processes and experiences possible in contemporary dance training. Essential technical and performance considerations are covered, including: breath; alignment; core activation; connectivity; dynamic qualities of motion; use of the body; use of space; action and finally, relationships to the audience.
Learning contemporary dance technique -- Essentials of good technique -- Graham technique -- Cunningham technique -- Release-based technique.
Includes bibliographical references and index.
Keywords: DANCE TECHNIQUE